Revised Guide on Resource Revenue Transparency. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The Guide, which is a companion document to the IMF's Code of Good Practices on Fiscal Transparency (2007), has been revised to reflect the new Code and to provide more recent examples of good practice by individual countries The Guide applies the good practices of the Code to the unique set of transparency issues faced by countries that derive a significant share of revenues from natural resources. It addresses issues arising both from the sheer size and volatility of such resources and the technical complexity of the transaction flows. The Guide supplements the Manual on Fiscal Transparency (2007).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet